(untitled) (Pedagogy of Higher and Secondary Education, 2012)
Sulima T. S. Industry higher education standards of the new generation - the key to training a professionally competent specialist The article is devoted to the peculiarities of higher education standarts work out on the basis of competence approach on the pattern of pedagogues’ training for professional teaching in civil engineering branch